Fourth Five-Year Plan Tamil Nadu Draft Annual Plan for 1970-71 - Planning Commission (Planning Commission, 1970)
Statement Showing the Details of Plan Schemes Under the Various Developmental and Group Heads, Outlay and Expenditure Programmes, Abstract Statement Showing the Details of Plan Schemes, Statement Showing the Details of Plan, Important Projects Costing Rs 5 Crores and Above, Check-List In Respect of Principal Projects Costing Rs 5 Crores and Above, Physical Programmes
Fourth Five-Year Plan Tamil Nadu Draft Annual Plan for 1970-71
Government of Tamil Nadu